Community empowerment based on utilization of livestock waste to become biogas in Bacukiki Energy Independent Village - Makmur Ahmad Husen; F. Firman; Ulfah Sarach Sheftiana; Muhammad Iqbal Hidayatulloh; ANR Relatami; Ifhan Dwinhoven (Universitas Muhammadiyah Malang, 2024)
Watang Bacukiki Village has a farm that produces cow manure but is not utilized. Cow manure (solid waste) eventually accumulates and creates an unpleasant odor. Based on these problems, PT Pertamina Patra Niaga Fuel Terminal Parepare carried out a CSR program by empowering the community, namely the Bacukiki Berdikari Energy Village as a form of assistance around the company's operational locations by building reactors so that cow manure does not pollute the environment and can be used as new, environmentally friendly energy, namely biogas, and compost. This program involves the community in processing cow manure. The research was carried out in collaboration with research centers, while data collection used observation, interviews, and surveys. The results of the biogas are used for household gas needs with the aim that the people in Watang Bacukiki Village can be energy independent through environmentally friendly energy that is self-produced through locally owned potential.